(untitled) (Research, Society and Development, 2021)
Invasive Mechanical Ventilation (IMV) is an artificial ventilatory treatment that is used in the Intensive Care Units (ICU) in severe cases of acute respiratory failure (ARI) or when the patient is unable to perform gas exchange properly, even with the oxygen supplementation. The aim of this review was to describe, based on the scientific evidence found in the literature, about nursing care for critically ill patients, in the prevention and treatment of ventilator-associated pneumonia (VAP). This is an integrative review, elaborated through searches carried out in the scientific databases: Database in Nursing (BDENF), Latin American and Caribbean Literature in Health Sciences (LILACS) and Scientific Electronic Library Online (SCIELO), using the keywords: “Pneumonia”, “Nursing” and “Intensive Care Unit”, including studies published from 2011 to 2020; (52) articles were grouped into thematic categories according to the different approaches of the studies regarding the process of pneumonia associated with mechanical ventilation, totaling a final sample consisting of (12) articles through the descriptive model with a qualitative approach. It was evident that the role of nurses in the care provided to VAP is extremely important, since qualified care, a good multidisciplinary relationship and the implementation of care packages are the most recommended measures in the literature, as it demonstrates better efficiency in care, thus favoring a decrease in the incidence rates of this involvement.